Genotypic and allelic frequencies of NPK8 1(rs28362491) variation in association with antropometric indices and lipid profile in Malay obese attributes - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Omar Alshajrawi, Mohd; Mohammad Ahmed, Isa (2018)
Obesity is a major health concern globally and in Malaysia 60% of the population aged more or equal lo 18 years is obese. NFKBl is a gene or interest interrelating obesity lo inflammatory path ways and can effect the nature of obesity and secondary disorders. Here we analyte the gentotypic and allelic frequency variation (rs28362491) in NFKB1 promoter region in a case control study comprising of a total of 180 subjects (90 obese and 90 non obese) from the record of Malaysian obesity DNA bank. We found according to the means of genotypic frequencies of NFKBl (rs28362491) variation in the sample group, II (insertion/insertion) was 32.2% as compared with the control group (l6.6%) in Malay attributes, and allelic frequencies were 78.8% I vs.67.7% D in obese group and in control group were 56.6% I vs. 83.3 D, while D is the wild type and I is the mutated allele.